Cork Tóstal Council (1955)
Group standing indoors, with Florence O'Donoghue sixth from the right, and Seán T. O'Kelly and his wife.
Stamp on verso: "Photograph by R. W. Hammond, 33, St. Patrick's Street, Cork.".
Keywords: O'Donoghue, Florence, -- 1895-1967; Ó Ceallaigh, Seán T. -- 1882-1966; Ryan, Phyllis, -- 1895-1983; Tóstal; Ireland -- History -- 1922-; Cork (Ireland); Photographic prints -- Irish -- 1950-1960